2014
DOI: 10.1021/nn503320m
|View full text |Cite
|
Sign up to set email alerts
|

Toward Omnidirectional Light Absorption by Plasmonic Effect for High-Efficiency Flexible Nonvacuum Cu(In,Ga)Se2 Thin Film Solar Cells

Abstract: We have successfully demonstrated a great advantage of plasmonic Au nanoparticles for efficient enhancement of Cu(In,Ga)Se2(CIGS) flexible photovoltaic devices. The incorporation of Au NPs can eliminate obstacles in the way of developing ink-printing CIGS flexible thin film photovoltaics (TFPV), such as poor absorption at wavelengths in the high intensity region of solar spectrum, and that occurs significantly at large incident angle of solar irradiation. The enhancement of external quantum efficiency and phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…However, the associated increase in the surface area increases the rate of minority carrier recombination on the surface regions. Recently, the use of metal nanoparticle plasmonics to improve the efficiency of solar cells has been extensively studied [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16]. The three well-known methods for increasing photocurrent in solar cells by the incorporation of metal nanoparticles are as follows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the associated increase in the surface area increases the rate of minority carrier recombination on the surface regions. Recently, the use of metal nanoparticle plasmonics to improve the efficiency of solar cells has been extensively studied [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16]. The three well-known methods for increasing photocurrent in solar cells by the incorporation of metal nanoparticles are as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Nahm et al incorporated Au nanoparticles with diameter of approximately 100 nm into titanium dioxide (TiO 2 ) thin films for use in dye-sensitized solar cells (DSSCs), and improved their power-conversion efficiency from 2.7% to 3.3% [6]. Chen et al demonstrated that Au plasmonic nanoparticles at the pn-junction interface of copper-indium-gallium-diselenide (CIGS) /cadmium sulfide (CdS) improved the efficiency of CIGS solar cells from 8.31% to 10.36% [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Thinning down these trapping architectures is not only for boosting their photoconversion efficiency but it can also open up the opportunity to exploit them in flexible, wearable photoelectronics. An ink‐printing CIGS based ultrathin flexible solar cell was proposed where the incorporation of nanoplasmonic units in the interface of pn junction have improved efficiency to a relatively high value of 10.36% (while the efficiency for bare structure was 8.31%) . This solar cell reveals near 80% flat EQE from 550 to 1100 nm.…”
Section: Light Trapping Schemesmentioning
confidence: 99%
“…Moreover, its band gap can be engineered by the partial substitution of indium by gallium, which further renders the flexibility of manipulating the optical absorption [1]. Nowadays, various methods for preparing CIGS absorber layers have been implemented, including vacuum processes (co-evaporation [2], sputtering [3], and pulsed laser deposition [4]) and nonvacuum processes (ink-printing [5] and electrochemical deposition [6]). However, the high quality CIGS thin films for laboratory-scale or module-level solar cells are usually prepared by co-evaporation or sputtering processes.…”
Section: Introductionmentioning
confidence: 99%